2016
DOI: 10.1021/acs.jafc.5b05320
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyaluronidase Activity in Vitro and Amelioration of Mouse Experimental Dermatitis by Tomato Saponin, Esculeoside A

Abstract: The increasing incidence of atopic dermatitis during recent decades has prompted the development of safe and effective agents for prevention of atopic diseases. Esculeoside A, a glycoside of spirosolane type, is identified as a major component in ripe tomato fruits. The present study investigated the effects of esculeoside A and its aglycon esculeogenin A on hyaluronidase activity in vitro and antiallergy in experimental dermatitis mice. Esculeogenin A/esculeoside A (esculeogenin A equivalent) with an IC50 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The methods described by Ndlovu et al [ 39 ] and Zhou et al [ 42 ] were applied for the hyaluronidase inhibition assay. Into 2 mL test tubes was placed: 50 μL of calcium chloride (12.5 mM), 50 μL of test samples or sodium aurothiomalate diluted in 0.1 M acetate buffer; pH 3.5 (with concentrations ranging between 9.4 and 150 μM), and 25 μL hyaluronidase (0.5 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The methods described by Ndlovu et al [ 39 ] and Zhou et al [ 42 ] were applied for the hyaluronidase inhibition assay. Into 2 mL test tubes was placed: 50 μL of calcium chloride (12.5 mM), 50 μL of test samples or sodium aurothiomalate diluted in 0.1 M acetate buffer; pH 3.5 (with concentrations ranging between 9.4 and 150 μM), and 25 μL hyaluronidase (0.5 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it was found that the intake of tomatine in mice led to a reduction in serum cholesterol, LDL cholesterol levels and ameliorated the severity of atherosclerotic lesions [53]. Similarly, esculeoside A also showed the ability to ameliorate hyperlipidemia and aterosclerosis [58] and block hyaluronidase activity and ameliorate the symptomatology of atopic dermatitis [59].…”
Section: Glycoalkaloidsmentioning
confidence: 99%
“…Competitive inhibition of hyaluronidase by esculeoside A Natural Product Communications Vol. 13 (11) 2018 1463…”
Section: Bmentioning
confidence: 99%
“…Esculeoside A is identified as a major component in ripe tomatoes [10], at 4-fold the content of lycopene, the main tomato carotenoid. We have previously reported [11] the ameliorating effects of esculeoside A on 2, 4-dinitrochlorobenzene (DNCB)-induced dermatitis of mice. We also found that esculeoside A potently inhibited hyaluronidase activity in vitro, but the analysis of inhibition mode is still lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation